Geotechnical properties of some organoclays - AKBULUT, SUAT; KURT, Z NESE; ARASAN, SERACETTIN; PEKDEMIR, YASEMIN (Sadhana (Bangalore), 2013)
The engineering characteristics of clay are dependant on its mineral and chemical structure. When the clay soils interacted with water, their volume and shear strength and compressibility properties change gradually. Large amount of decrease in terms of the shear strength of clay soils due to swelling is observed. In order to solve these problems, the stabilization of clay soils using chemical additives is a prevalent subject of research. In view of this, previous research studies have employed surface active surfactants to modify the fundamental properties of soft clays. In this study, surfactant–clay complexes (organoclays) were developed using a raw clay modification with four surfactants and their geotechnical properties were determined in laboratory conditions. Two of the surfactants are cationic (cetyl trimethyl ammonium chloride, denoted as CTAC and quaternised ethoxylated fatty amine, denoted as QEFA) and the others are anionic (linear alkylbenzene sulphonic acid, denoted as LABSA and sodium lauryl ether sulfate, denoted as SLES). The experimental results indicated that the geotechnical properties of organoclays show significant change when compared to those of natural clay. The specific gravities, unconfined compression strengths and maximum dry densities of all organoclays were decreased. Optimum moisture content and swelling pressure values were decreased in cationic surfactant modified clays. However, the optimum moisture content and swelling pressure values of anionic surfactant clays are increased. A direct shear test was performed to determine the shear strength of organoclays. The test results also showed that the internal friction angles of organoclays were increased. Additionally, the change in the hydraulic conductivity was found to be insignificant.